Pengaruh Harga dan Lokasi terhadap Keputusan Pembelian Rumah di Kawasan Perumahan - Didit Darmawan; Suzakqi Arjun Ishari; Muhammad Arya Pramudya (Pusat Riset dan Inovasi Nasional, 2026)
The need for housing is increasingly pressing with population growth and urbanization, while affordability remains a challenge for single-income households. The purpose of this investigation is to assess the impact of price also location on home purchase decisions using a literature review. This approach involves reviewing, analyzing, and synthesizing various relevant literature sources, such as scientific journals, books, undergraduate theses, also previous investigation reports that discuss factors influencing home purchase decisions. The study concludes that price plays a positive also significant role in home purchase decisions, as consumers prefer homes with prices commensurate with their purchasing power and the quality offered. Location has also been shown to influence decisions, particularly when housing is conveniently situated at a key location and the availability of public facilities. However, certain studies indicate that price and location are not always the primary determinants of decision-making, as other variables such as promotion, brand image, product quality, and lifestyle also play a role.